Three Phase Two Leg Neutral Point Clamped Converter with output DC Voltage Regulation and Input Power Factor Correction - Bogimi Sirisha; P. Satish Kumar; N. Susheela (Institute of Advanced Engineering and Science, 2012)
In this paper, a three-phase two leg neutral point clamped (NPC) converter is presented for power factor correction and dc-link voltage regulation. The adopted converter has simpler circuit configuration and less number of power switches compared to three-level PWM converter. In this circuit configuration, only eight power switches and four clamping diodes with voltage stress of half the dc bus voltage are used. A simplified space vector pulse width modulation scheme (SVPWM) is also adopted to track the line current commands. A reference voltage vector is generated on the ac terminal for drawing the sinusoidal line currents with unity power factor. This algorithm reduces the time required to calculate the switching time durations of voltage vectors. The simulation results have been presented to verify the validity and effectiveness of the proposed control strategy.DOI: http://dx.doi.org/10.11591/ijpeds.v2i2.226